MAKNA TAK TUNGGAL DALAM BAHASA PERANCIS - Rahayu, Siti Perdi (Jurnal Penelitian Humaniora, 2015)
Abstract This research is aimed at describing the form of French linguistic units, which express non-singular meanings. It also attempts to explain the semantic markers employed to express such meanings. The data collection is done through observation using non-active participation and field notes. The data then is descriptively analyzed by classification. The meanings of the non-singular linguistic units can be grouped into 1) the non-singular meaning based on word category and word sub-category 2) the non-singular meaning based on numbers 3)the non-singular meaning based on the process, and 4)the semantic markers which express the non-singular meanings. The result shows that the non-singular meanings only appear in pronouns and nouns. Based on the number, the non-singular meanings fall into finite and non-finite categories. They can also be classified as lexical and grammatical. The semantic markers determining the non-singular meanings can be grouped into inflectional affixes, determinants, zeros and contexts. Keywords: French, non-singular meaning, semantic-marker